Assessment of 16 different herbs for their suitability as antioxidant rich microgreens - PUNASIA, MANOJ; AGNIHOTRI, ROSHNI; SINGH, HEMLATA (The Indian Journal of Agricultural Sciences, 2026)
The study on microgreens was carried out during the year 2023–24. Sixteen vegetable microgreens were evaluated for morphological, sensory and biochemical traits. Significant variations were observed in growth characteristics, with radish demonstrating the fastest germination (2.30 days) and highest germination % (94.10%). Broccoli had the longest stem length (10.20 cm), while celery had the shortest (3.93 cm). Biochemical analysis revealed significant variations in chlorophyll content, with fenugreek (58.77 mg/100g FW) and radish (57.03 mg/100g FW) having the highest levels. Total phenol content was highest in fenugreek (6.59 mg GAE/g) and Brussels sprouts (6.44 mg GAE/g). Antioxidant activity, measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Ferric Reducing Antioxidant Power (FRAP) assays. Lower DPPH activity showed strong antioxidant potential in fenugreek (98.52 µg/ml) and carrot (98.66 µg/ml). While, high FRAP values indicated strong antioxidant capacity as evident in radish (18.66 µ mol TE/g) and carrot (15.65 µ mol TE/g). Sensory evaluation on 9 point hedonic scale showed overall acceptability ranging from 5.5–9.0, with lettuce receiving notably low scores. The study highlights the diversity and potential of microgreens as a rich source of antioxidants and other beneficial compounds.